La décrétale Ad Gallos episcopos, son texte et son auteur : texte critique, traduction française et commentaire - Duval, Yves-Marie. (Vigiliae Christianae, Supplements, 2005)
In 1904, Ed.-Ch. Babut issued a new edition of the important Decretale Ad Gallos episcopos with the help of a second manuscript of the canonical "collection of St. Maur". He attributed it to Pope Damasus (366-384), and not to Sirice (384-398). Nevertheless, he did ignore the existence of the ancestor of the two previous manuscripts and of an other collection, materialized today by two fragmented manuscripts. This new edition of the Decretale is updated with the help of all the existing traditions and brings significant improvements. The attribution to Damasus, discussed throughout the 20th century is here confirmed through another method than Babut's. The survey of the content, the texts of the holy scripture used, and argumentation make possible the identification of the influence of Jerome who was the secretary of Damasus in 382-384. He was the only man using specific bible texts or specific expressions present in this Decretale. In spite of his wish to base all his decisions upon the Scripture and upon the Fathers' tradition (Nicée-Sardique), we discover in this decretale, focused essentially on the life of the blessed virgins and on the hiring process and life of the church, the strong assessment of the power of the "Sedes apostolica" and also of the necessity of a discipline policy, designed by the Church of Rome.